2017
DOI: 10.1073/pnas.1613305114
|View full text |Cite|
|
Sign up to set email alerts
|

Active MLKL triggers the NLRP3 inflammasome in a cell-intrinsic manner

Abstract: Necroptosis is a physiological cell suicide mechanism initiated by receptor-interacting protein kinase-3 (RIPK3) phosphorylation of mixed-lineage kinase domain-like protein (MLKL), which results in disruption of the plasma membrane. Necroptotic cell lysis, and resultant release of proinflammatory mediators, is thought to cause inflammation in necroptotic disease models. However, we previously showed that MLKL signaling can also promote inflammation by activating the nucleotide-binding oligomerization domain (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
318
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(331 citation statements)
references
References 63 publications
11
318
1
1
Order By: Relevance
“…A link between the NLRP3 inflammasome and the necroptotic cell death pathway has emerged. In response to necroptotic activators, the kinase RIPK3 and the necroptotic effector MLKL are required to activate the NLRP3 inflammasome and induce IL‐1β release . In this case, MLKL oligomerizes on the cell membrane to induce pore formation, resulting in necroptosis and a reduction in the level of intracellular potassium triggering activation of the NLRP3 inflammasome .…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…A link between the NLRP3 inflammasome and the necroptotic cell death pathway has emerged. In response to necroptotic activators, the kinase RIPK3 and the necroptotic effector MLKL are required to activate the NLRP3 inflammasome and induce IL‐1β release . In this case, MLKL oligomerizes on the cell membrane to induce pore formation, resulting in necroptosis and a reduction in the level of intracellular potassium triggering activation of the NLRP3 inflammasome .…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
“…In this case, MLKL oligomerizes on the cell membrane to induce pore formation, resulting in necroptosis and a reduction in the level of intracellular potassium triggering activation of the NLRP3 inflammasome . Of particular interest is that MLKL‐dependent secretion of IL‐1β does not rely on the pyroptosis executor gasdermin D, suggesting that IL‐1β might be released through MLKL‐induced pores instead. These studies further accentuate the complex interplay between the NLRP3 inflammasome and nonpyroptotic cell death pathways.…”
Section: Canonical Nlrp3 Inflammasomementioning
confidence: 99%
“…The kinase activity of RIPK1 and RIPK3 is not required for this atypical non-apoptotic caspase-8 activation and in fact, treatment of cells with a RIPK3 kinase inhibitor enhances LPS-induced caspase-8 activation and thus IL-1β processing (101). Furthermore, recent studies have demonstrated an additional link between necroptosis in inflammasome activation, by showing that MLKL activation, which leads to membrane disruption, can activate the NLRP3 inflammasome in a cell-intrinsic manner by altering ion homeostasis (102, 103). This finding implies that induction of necroptosis is linked inextricably to inflammasome assembly, and that caspase-1 activation and processing of IL-1β and IL-18 likely accompany necroptotic cell death when all are present.…”
Section: The Role Of Ripk3 In Inflammationmentioning
confidence: 99%
“…RIPK3 is required within the hematopoietic cells to induce reparative programming through IL‐1β/IL‐23‐induced IL‐22 production . RIPK3 promotes inflammasome activation and IL‐1β release in cells of the innate immune system . Consistent with this innate cell‐intrinsic role of RIPK3, RHIM‐domain‐mediated cytokine production within the dendritic cell compartment (CD11c) and not the kinase activity (necroptosis) is required for protection against DSS‐induced damage .…”
Section: Necroptosis In the Gutmentioning
confidence: 92%